Antibiotic Resistance in Paediatric Febrile Urinary Tract Infections. (June 2022) - Esposito, Susanna; Biasucci, Giacomo; Pasini, Andrea; Predieri, Barbara; Vergine, Gianluca; Crisafi, Antonella; Malaventura, Cristina; Casadio, Luca; Sella, Marcello; Pierantoni, Luca; Gatti, Claudia; Paglialonga, Letizia; et al.
Highlights: Febrile urinary tract infection (UTI) is the most frequent cause of serious bacterial illness in children aged <2 years. Empiric antibiotic treatment must be initiated soon after a urine specimen for culture has been obtained. The increase in antibiotic resistance of uropathogens requires continuous monitoring. To limit the emergence of resistance, every effort to reduce and rationalize antibiotic consumption must be made. An increased use of antibiotic stewardship can be greatly effective for antibiotic resistance. Abstract: Febrile urinary tract infection (UTI) is currently considered the most frequent cause of serious bacterial illness in children in the first 2 years of life. UTI in paediatrics can irreversibly damage the renal parenchyma and lead to chronic renal insufficiency and related problems. To avoid this risk, an early effective antibiotic treatment is essential. Moreover, prompt treatment is mandatory to improve the clinical condition of the patient, prevent bacteraemia, and avoid the risk of bacterial localization in other body sites. However, antibiotic resistance for UTI-related bacterial pathogens continuously increases, making recommendations rapidly outdated and the definition of the best empiric antibiotic therapy more difficult. Variation in pathogen susceptibility to antibiotics is essential for the choice of an effective therapy. Moreover, proper identification of cases at increased risk of difficult-to-treat UTIs can reduce the risk of ineffective therapy. In this review, the problem of emerging antibiotic resistance among pathogens associated with the development of paediatric febrile UTIs and the best potential solutions to ensure the most effective therapy are discussed. Literature analysis showed that the emergence of antibiotic resistance is an unavoidable phenomenon closely correlated with the use of antibiotics themselves. To limit the emergence of resistance, every effort to reduce and rationalise antibiotic consumption must be made. An increased use of antibiotic stewardship can be greatly effective in this regard.